2023
DOI: 10.1002/hec.4693
|View full text |Cite
|
Sign up to set email alerts
|

Risk aversion and COVID‐19 vaccine hesitancy

Abstract: We here investigate the role of risk aversion in COVID‐19 vaccine hesitancy. The theoretical effect is ambiguous, as both COVID‐19 infection and vaccination side‐effects involve probabilistic elements. In large‐scale data covering five European countries, we find that vaccine hesitancy falls with risk aversion, so that COVID‐19 infection is perceived as involving greater risk than is vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Higher risk aversion in vaccinated participants suggests that these participants viewed contracting COVID-19 as a larger risk and, therefore, were more likely to receive the full dose. These findings are consistent with those of a study by Lepinteur et al [ 58 ], who found that risk-averse individuals were more likely to accept the COVID-19 vaccination, indicating that the perceived risk of contracting COVID-19 was greater than any risk from the vaccine. Hudson and Montelpare [ 54 ] also found that risk aversion may promote vaccine adherence when people perceive contracting a disease as more dangerous or likely.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Higher risk aversion in vaccinated participants suggests that these participants viewed contracting COVID-19 as a larger risk and, therefore, were more likely to receive the full dose. These findings are consistent with those of a study by Lepinteur et al [ 58 ], who found that risk-averse individuals were more likely to accept the COVID-19 vaccination, indicating that the perceived risk of contracting COVID-19 was greater than any risk from the vaccine. Hudson and Montelpare [ 54 ] also found that risk aversion may promote vaccine adherence when people perceive contracting a disease as more dangerous or likely.…”
Section: Discussionsupporting
confidence: 92%
“…Relatively few studies have sought to predict COVID-19 vaccine uptake using machine learning approaches [ 8 , 59 ]. Given that a small set of studies has assessed the psychological basis that may underlie vaccine uptake and choices [ 6 , 52 , 53 , 56 , 58 , 59 , 83 ], but none have used computational cognition variables based on reward and aversion judgment to predict vaccine uptake , we sought to assess whether variables quantifying human judgment predicted vaccine uptake . This study found that 7 demographic and 15 judgment variables predicted vaccine uptake with balanced and moderate recall and specificity, moderate accuracy, high AUROC, and high precision using a BRF framework.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third population group consists of risk-averse individuals who perceive vaccination-related adverse events to be common or serious [ 6 ]. These individuals include those with prior severe drug-, food-, or insect sting-related allergic reactions like anaphylaxis, who were found by Asperti and colleagues to be more anxious when receiving COVID-19 vaccination compared with those with a mild allergy.…”
mentioning
confidence: 99%